Measuring outcomes on a Medical Psychiatric Unit: HoNOS, , CANSAS and costs. (October 2019) - Jansen, L.; Hunnik, F.; Busschbach, J.J.V.; Lijmer, J.G.
Highlights: 82% of all patients admitted to the MPU had a very severe functional status based on the HoNOS. MPU treatment resulted in a decrease of 93 (44.7%) unmet needs, resulting in costs of claims of €6.880 per decreased unmet need. MPU admission resulted in a decrease of 232 (28.6%) points on the HoNOS scale, resulting in costs of claims of €2.842 per decreased HoNOS point. Abstract: Objective: To study the course of the functional status and healthcare needs of patients on a Medical Psychiatric Unit (MPU). Methods: In a single-centre observational prospective design the Health of the Nation Outcome Scales (HoNOS) and Camberwell Assessment of Needs Short Appraisal Schedule (CANSAS) instruments were administered at admission and discharge. Functional status and healthcare needs were assessed utilizing the HoNOS and CANSAS respectively. The total costs of healthcare claims related to the admission were calculated based on claims data. Results: In total 50 patients were included with a mean improvement of 4.6 on the HoNOS and an effect size of 0.6.The total number of unmet needs fell from 208 to 115. The median costs per decreased HoNOS point were €2.842 and €6.880 per unmet need. Discussion: Many patients improved, but due to a large standard deviation at baseline and a low Cronbach's alpha, only 4 patients showed a reliable improvement on functional status. That substantial remission was achieved was shown by the decrease in unmet needs of 93 (44.7%) for the whole group. These observations support the implementation of MPUs, although more research is warranted to ensure cost-effectiveness.